Challenging The City Scale, Bilbao (2018)
From the outset Bilbao Ekintza decided to partner with URBANBAT, an office of urban innovation run by Maria Arana Zubiate. It aims to “bring together local communities and experts like architects, artists and designers to tackle challenges in the area.” Bilbao Ekintza and URBANBAT joined forces to achieve the common goal of improving the image and the atmosphere of San Francisco, Bilbao La Vieja and Zabala. “Because we organise an annual festival and a lot of workshops with residents, we had already identified several social and urban issues in our collaborative workshops and laboratories,” Maria Arana Zubiate says. “One of them was that women weren’t present enough in the streets.” And indeed, men hang around in the streets in the evening and women sometimes do not feel safe, even though the area has a vibrant nightlife. “Another problem was the obvious sociological separation between the three neighbourhoods.”